The Mobile Web Comes of Age. - Vaughan-Nichols, S.J. (Computer (00189162), 2008)
Early mobile browsers offered minimal functionality and thus were not that popular with users accustomed to desktop browsers' capabilities. The mobile Web has moved forward largely because wireless-access technologies have advanced. Today's mobile browsers work with the same Web-based technologies as PC-based browsers, including PDF code and JavaScript.